Pufnstuf [videorecording (DVD)] - Rose, Si; Murray, John Fenton, 1917-1996; Wild, Jack, 1952-2006; Hayes, Billie; Raye, Martha; Elliot, Cass, 1941-1974 (World of Sid & Marty Krofft, 2009)
Jimmy is lured aboard a magical talking boat sent by an evil witch named Witchiepoo after school one day. The evil witch wants to make him a prisoner and steal his magic flute. But H.R. Pufnstuf and his friends come to the rescue!